Medical oncological treatment for patients with Gastrointestinal Stromal Tumor (GIST) – A systematic review. (April 2022) - Brinch, Charlotte Margareta; Aggerholm-Pedersen, Ninna; Hogdall, Estrid; Krarup-Hansen, Anders
Abstract: Background: Chemotherapy is ineffective in treating patients with Gastrointestinal Stromal Tumor (GIST). However, several types of tyrosine kinase inhibitors have been investigated since the approval of imatinib in 2001. The purpose of this report was to systematically review studies on the efficacy of neoadjuvant, adjuvant, and lifelong medical oncological treatment of GIST. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed throughout the review process. The protocol was submitted to the International prospective register of systematic reviews database (ID 251724). A systematic literature search was performed, including phase II- and III studies of biological treatment, reporting on treatment effect in patients with GIST. Results: Of 308 identified publications, 42 studies were included in this review. Conclusion: This review gives an overview of the existing evidence for approved lines of oncological treatments and potential alternatives for patients with GIST in the neoadjuvant-, adjuvant- and life-long setting. Graphical Abstract: ga1 Highlights: Gastrointestinal Stromal Tumor (GIST) is a mesenchymal tumor. Neoadjuvant treatment is manageable for patients with GIST. Three years adjuvant treatment is recommended for patients with high-risk GIST. For patients with advanced GIST there are three approved lines of treatment.